The Impact of Antecedent of Service Quality on Customers Satisfaction in Saudi Arabia - Alawni, Mohammed Saad; Al-Matari, Ebrahim Mohammed; Senan, Nabil Ahmed M. (CENTRAL ASIA AND THE CAUCASUS, 2021)
This study is an attempt to examine the association between antecedents of service quality and customers satisfaction in Saudi Arabia companies. This study applied Statistical Package for the Social Sciences (SPSS) to test the connection between antecedents of service quality and customers satisfaction. The study sample consisted of 339 individuals from Saudi insurance companies and data was obtained from them with the help of questionnaires. The questionnaire was developed based on prior studies as elaborated in the methodology chapter. In addition, this study revealed a positive significant relationship between antecedents of service quality and customer satisfaction. Furthermore, this study is expected to contribute to the theoretical, practical and policy market that may work together to bring about improved customer satisfaction. In the last part of this study, study limitations and future recommendations were enumerated.